2014
DOI: 10.1134/s0018143914050129
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrous acid formation induced by air spark plasma radiation

Abstract: The reaction of the stable free radical diphenylpicrylhydrazyl (DPPH • ) with water treated by plasma radiation of air spark discharge immediately after irradiation and for 13 days after irradiation has been studied. The choice is due to the fact that peroxynitrous acid ONOOH, which can be generated by irradia tion, is a donor of atomic hydrogen and the reaction with DPPH • allows the acid concentration to be deter mined. The formation of ONOOH has been detected by the 4th day after the treatment, [ONOOH] = (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Therefore, this parameter must be monitored during plasma treatments because its value is affected by the discharge operation. The decreasing pH value of solutions treated by the WFF DBD system is caused by acidic substances such as nitric acid, nitrous acid, and peroxynitrous acid which are produced during the discharge process in air above the water film. However, contribution of peroxynitous acid to the acidity increase is weak because of its short lifetime and a relatively high pKa value of 6.8.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this parameter must be monitored during plasma treatments because its value is affected by the discharge operation. The decreasing pH value of solutions treated by the WFF DBD system is caused by acidic substances such as nitric acid, nitrous acid, and peroxynitrous acid which are produced during the discharge process in air above the water film. However, contribution of peroxynitous acid to the acidity increase is weak because of its short lifetime and a relatively high pKa value of 6.8.…”
Section: Resultsmentioning
confidence: 99%
“…21 This reaction is probably important in cellular reactions coupled to oxidative stress and NO control mechanisms. 22,23 It has been shown that peroxynitrite can isomerize into nitrate (NO 3 À ) in solution, in a reaction that is exothermic by 161 kJ mol À1 . 24,25 In general, ionic reactions, including ion-molecule reactions, are essential to atmospheric chemistry; [26][27][28][29] the significance of atmospheric ions should be emphasised since they also serve as condensation nuclei for water in the atmosphere.…”
mentioning
confidence: 99%